An Analysis of Students’ Errors in Solving Systems of Linear Equations in Two Variables (SPLDV) Based on Polya’s Steps - Eka Fadhilah Apriliani; Sintha Sih Dewanti (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2026)
This study aims to determine the types of errors students make when solving systems of linear equations with two variables (SPLDV) as viewed through Polya’s steps. Polya’s problem-solving steps consist of understanding the problem, making a plan, carrying out the plan, and checking the solution. This study employs a qualitative descriptive approach with a sample of 25 eighth-grade students at a public junior high school in Depok, Yogyakarta. Data were collected by administering a diagnostic test. The research instrument consisted of a written test comprising two problems covering the topic of two-variable linear systems of equations. The findings indicate that students’ errors were distributed across all of Polya’s steps, with the following percentages: understanding the problem (46%), planning (52%), implementing the plan (66%), and checking the results (82%). The types of errors made by students included errors in writing down known and unknown information, errors in algebraic calculations, incomplete solution steps, and a tendency not to check their answers.